2014
DOI: 10.1371/journal.pmed.1001723
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence and Reproductive Coercion: Global Barriers to Women's Reproductive Control

Abstract: Jay Silverman and Anita Raj discuss the policies and interventions required to address the range of poor reproductive outcomes for women and adolescents, including loss of reproductive control, associated with intimate partner violence. Please see later in the article for the Editors' Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
121
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(128 citation statements)
references
References 25 publications
5
121
1
1
Order By: Relevance
“…Given the ample evidence that men and norms of masculinity play a critical role in women’s contraceptive use and family planning outcomes (Barua et al, 2004; M. Greene & Barker, 2011; Pachauri, 2014; Raj & McDougal, 2015; Raju S, 2000; Silverman & Raj, 2014), the field could adopt gender-transformative strategies that have been used elsewhere to prevent HIV transmission and violence perpetration (Dworkin et al, 2015; Dworkin et al, 2013). Interventions like CHARM and the Malawi Male Motivator project are just initial steps to integrate gender-transformative approaches more fully into family planning interventions (D.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the ample evidence that men and norms of masculinity play a critical role in women’s contraceptive use and family planning outcomes (Barua et al, 2004; M. Greene & Barker, 2011; Pachauri, 2014; Raj & McDougal, 2015; Raju S, 2000; Silverman & Raj, 2014), the field could adopt gender-transformative strategies that have been used elsewhere to prevent HIV transmission and violence perpetration (Dworkin et al, 2015; Dworkin et al, 2013). Interventions like CHARM and the Malawi Male Motivator project are just initial steps to integrate gender-transformative approaches more fully into family planning interventions (D.…”
Section: Discussionmentioning
confidence: 99%
“…Greene & Barker, 2011; Pachauri, 2014; Raju S, 2000). Husbands can prevent – through the use of coercive control and/or emotional/physical/sexual violence – their wives from adopting modern contraceptive use or from correctly using a form of contraception (Raj & McDougal, 2015; Silverman & Raj, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…In this review the authors define RC more widely than many others, in the context of gendered control, coercion and violence 8. RC fundamentally interferes with women’s reproductive autonomy generally9 and with their autonomous sexual decision-making more specifically 10. Reproductive coercion is a subset of RC and occurs when a credible threat of harm or force is made to control a woman 5 11.…”
Section: What Is Reproductive Control?mentioning
confidence: 99%
“…Intimate partner violence (IPV) negatively impacts women's health and well‐being and is a major contributor to poor reproductive health . Globally, 30% of ever‐partnered women experience physical or sexual IPV during their lifetimes .…”
Section: Introductionmentioning
confidence: 99%
“…In the context of IPV, a diminished sense of reproductive agency could prompt women to perceive more limited access to contraception, with IPV victims less able to use contraception effectively owing to refusal by partners and contraceptive sabotage . Discordance in fertility intentions within the family, the most common form being more pro‐natalist preferences on the part of the husband/partner, has been shown to be associated with increased fertility, and could be indicative of pressure from the husband/partner either to continue a pregnancy that a woman wishes to terminate or to terminate a pregnancy that she wishes to continue . Less is known about discordance in fertility intentions of in‐law relatives but recent studies in Côte d'Ivoire have reported high rates of in‐law abuse and reproductive control, as well as co‐occurrence between IPV and in‐law perpetrated reproductive coercion, highlighting the influence of in‐laws and suggesting that multiple layers of reproductive control can be present within the family.…”
Section: Introductionmentioning
confidence: 99%